Explorando o Papel da Estrutura de Propriedade nas Decisões sobre Práticas de Responsabilidade Social Corporativa Voltadas aos Empregados - Goes Pinheiro, Bruno; Alves Soares, Romulo; Cavalcanti Sá de Abreu, Mônica (Review of Business Management, 2022)
Purpose – To analyze the effect of different ownership structures on employeeoriented corporate social responsibility (CSR). Theoretical framework – Agency theory is adopted to explain how the ownership structure is capable of changing the intensity of implementation of CSR practices aimed at employees. Design/methodology/approach – The sample comprises companies listed on the Brasil, Bolsa, Balcão (B3) between 2010 and 2018. The data collection used the reference form from the B3, Economática®, and CSRHub as sources, and the multiple linear regression method of generalized least squares. Findings – The study identifies different strategic orientations according to ownership concentration and the identity of the controlling shareholder. Family and state-owned companies do not seem motivated to develop CSR practices aimed at employees, while multinational companies assume that these practices should be implemented. Practical & social implications of research – The research contributes to understanding the behavior of different ownership identities, which can lead to different patterns of adoption of CSR practices aimed at employees. Originality/value – The study identified different strategic CSR orientations, according to ownership concentration and the identity of the controlling shareholder. Family and state-owned companies do not seem motivated to develop CSR practices aimed at employees, while multinational companies assume the importance of these practices. Companies with institutional ownership do not have clearly defined behavior in terms of CSR. These different results seem to show that the path towards a proactive approach to CSR in Brazil is “long and tortuous,” especially due to the incipient mechanisms of corporate governance. Keywords: Ownership structure, corporate social responsibility, employees, corporate governance, stakeholders.